2021
DOI: 10.3389/fpls.2021.751372
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cell Wall Modifying Proteins Regulate Wall Mechanics to Steer Plant Morphogenesis

Abstract: Plant morphogenesis involves multiple biochemical and physical processes inside the cell wall. With the continuous progress in biomechanics field, extensive studies have elucidated that mechanical forces may be the most direct physical signals that control the morphology of cells and organs. The extensibility of the cell wall is the main restrictive parameter of cell expansion. The control of cell wall mechanical properties largely determines plant cell morphogenesis. Here, we summarize how cell wall modifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…It has been shown that homogalacturonan (HG), the most abundant pectin subtype in plant cell walls, is synthetized as methylesterified polymer ( 18 ). De-methylesterification of HG by PMEs can lead to its degradation by PLs and influence cell wall integrity ( 19 ), thus being a primary suspect in the elimination of the nucellus and therefore the focus of our investigation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that homogalacturonan (HG), the most abundant pectin subtype in plant cell walls, is synthetized as methylesterified polymer ( 18 ). De-methylesterification of HG by PMEs can lead to its degradation by PLs and influence cell wall integrity ( 19 ), thus being a primary suspect in the elimination of the nucellus and therefore the focus of our investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Pb may affect the autolytic activity of the cell wall. Plant cell walls contain various kinds of enzymes that are involved in cell wall remodeling [ 51 , 52 ]. Since Pb is able to bind to acidic sugar residues of matrix polysaccharides [ 23 , 46 ], it is likely that Pb accumulated within the cell walls may interfere with the action and activity of enzymes involved in the degradation of cell wall polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ACC decreased the total extensibility, although it was corrected for cross-sectional area ( Figure 2 B). The cell wall extensibility is a growth-limiting factor affecting the elongation growth of plants [ 3 ]. Collectively, these findings suggest that ACC suppresses the elongation growth of azuki bean epicotyls by decreasing the cell wall extensibility.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of the cell wall to extend (extensibility of cell walls) determines the rate of elongation growth of individual cells; therefore, it regulates the elongation growth of the whole plant [ 3 ]. Ridge (1973) [ 4 ] reported that ethylene decreased the extensibility of cell walls, which was determined by a plasmolytic method during the inhibition of elongation growth of pea epicotyls.…”
Section: Introductionmentioning
confidence: 99%